REVENUE SYSTEMS IN THE NEW SCHOOL STUDENT CULTURAL JAKARTA USING MICROSOFT ACCESS - Sri Rejeki; Sahni D.P, SKom, MM Sahni D.P, SKom, MM (Jurnal Sistem Informasi, 2002)
The use of computers as a tool for input data so that prospective students are able to help the new student officer to obtain and provide information on the results of data processing.Farmingis the foundation of institutions conducting teaching and learning activities at the school was a lot happening recording transactions such as recording student data, registration fee payments, payment of school orientation period, payment of entrance fee, tuition fee payment from the junior level, vocational school, high school. Currently still using the manual as its data storage.The existence of computerization with Microsoft Access applications in data processing prospective students, transactions, new students and prospective students in making reports, transaction reports, reports of new students who received the head of the foundation to be effective.